How individuals with body dysmorphic disorder (BDD) process their own face: a quantitative and qualitative investigation based on an eye-tracking paradigm. Issue 3 (4th May 2017) - Toh, Wei Lin; Castle, David J.; Rossell, Susan L.
ABSTRACT: Introduction: Body dysmorphic disorder (BDD) is characterised by repetitive behaviours and/or mental acts occurring in response to preoccupations with perceived flaws in physical appearance. Based on an eye-tracking paradigm, this study aimed to examine how individuals with BDD processed their own face. Methods: Participants were 21 BDD patients, 19 obsessive–compulsive disorder patients and 21 healthy controls (HC), who were age-, sex-, and IQ-matched. Stimuli were photographs of participants' own faces as well as those from the Pictures of Facial Affect battery. Outcome measures were affect recognition accuracy as well as spatial and temporal scanpath parameters. Results: The BDD group exhibited significantly decreased recognition accuracy for their own face relative to the HC group, and this was most pronounced for those who had a key concern centred on their face. Individual qualitative scanpath analysis revealed restricted and extensive scanning behaviours in BDD participants with a facial preoccupation. Persons with severe BDD also exhibited more marked scanpath deficits. Conclusions: Future research should be directed at extending the current work by incorporating neuroimaging techniques, and investigations of eye-tracking focused on affected body parts in BDD. These could yield fruitful therapeutic applications via incorporation with existing treatment approaches.